Gaya Hidup Mahasiswa Universitas Pamulang dari Perspektif Beauty Influencer di Instagram - Panji Nurswasono; Chandriana Alfarizi; Sri Fuji Sujati (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
This study aims to determine whether the influence of beauty influencer decisions on Instagram on the lifestyle of Pamulang University female students. The type of research used was Quantitative Research with respondents taken from 2020 and 2021 cohort students from 1 faculty of Pamulang University which were a factor in this study with 101 respondents obtained in the study exceeding the number of samples needed by researchers of 100 respondents from 1,253 populations. Data were obtained by distributing questionnaires to respondents who were distributed by researchers. By processing data using simple linear regression analysis, testing hypotheses, testing the coefficient of determination, and testing classical assumptions as data studies with the help of the SPSS ver 22 program. The results showed that beauty influencers were significantly Partially influenced positively and did not significantly influence the lifestyle of female students. The results of the study showed that beauty influencers influenced the lifestyle of female students at Pamulang University by 0.718 or 71.8% as seen from Adjust R Square while the remaining 29.2% were influenced by other factors.